Control of cracking in partially prestressed post-tensioned beams. - Abdus Salam, S.K.; Abang Ali, Abang Abdullah; Shamsul Alam, K. H.; Syed Mansur, Syed Junid (1986)
The primary objective of this paper 15 to discuss the serviceability behaviour of partially prestressed concrete beams. Seven simply supported rectangular beams were tested on an effective span of 2.745m subjected to two third point loadings. The variables in these post-tensioned model beams were the amount of prestressing wires and bonded deformed bar. The effect of bond of the prestressing wires was also investigated by making four of the beams bonded by using pressurised grouting while three others were tested unbonded. Crack width and deflection were recorded at each loading increment and crack propagations observed. The results obtained were compared with theoretical values proposed by various authors. The results are also compared with the service limit criteria for cracking and deflection according to the British Standards Code of Practice CP 110 : 1972. It was observed that the service limit criteria for cracking and deflection as set out by the Code are too conservative for the rectangular beams tested. The existing theory under-estimates the ultimate as well as the service load carrying capacity as is the case in other reinforced and prestressed structural elements. The Code over-estimates the crack width of partially prestressed concrete beams resulting in the actual crack width being smaller than the permissibile value of O.2mm at service· loading. The nature of bonding has a great influence on crack widths and deflections. Bonded beams greatly improve on serviceability by having increased load carrying capacity and reduced crack width whereas the number of cracks in unhanded beams is fewer and wider resulting in increased deflection and reduced ultimate moment.